السلوك والدافعية لدى مرشدي السياح الماليزيين عند التعامل مع السياح العرب في كوالا لمبور - Nurul Syuhadah binti Yahya
This study aims to know the attitude and motivation among tourist guide towards dealing with arabic tourist. This research is using interview session with 6 tourist guide that works in Kuala Lumpur by taking the views and to analyse their attitude and motivation towards dealing with arabic tourist. The researcher used qualitive methodogy approach and in-depth interview to get the accurate data from respondents. The researcher use Atlas.ti as a collecting tools data. The finding of the study indicated that the attitude among tourist guide positive and high motivation while dealing with arabic tourist. Therefore, this study suggests tour guides to improve positive attitude and high motivation to develop islamic tourism industry in Malaysia.